Project Manager Competencies for Dealing with Socio-Technical Complexity: A Grounded Theory Construction - Navid Ahmadi Eftekhari; Saba Mani; Javad Bakhshi; Sahar Mani (Systems, 2022)
An ongoing question is what constitutes the characteristics of a project manager. This is the subject of many studies. The characteristics, skills, abilities and knowledge of project managers—essential factors in a project’s success—describe their level of competency. This study aims to assess the relationship between project manager competencies and project complexity in the information technology (IT) sector. In total, 21 semi-structured interviews were conducted with senior practitioners associated with complex IT projects in the private and public sectors. All transcripts were analysed through grounded theory and content analysis, with experts approving the results. Our study identified 41 competencies within project complexity, with these grouped under the following 10 dimensions: project management (PM) knowledge; management skills; interpersonal skills and attributes; professionalism; expertise; emotional skills; contextual skills; influencing skills; team working; and cognitive skills. According to this research, leadership is the core competency of a project manager, while project management knowledge is the most essential of these competency dimensions. This study’s findings can assist both academics and practitioners in simplifying the complexity of projects and helping to achieve a project’s objectives.